Физико-химические свойства новых марок алмазных нанопорошков детонационного синтеза - Новиков, Н.В.; Богатырева, Г.П.; Маринич, М.А.; Олейник, Н.А.; Базалий, Г.А.; Заика, Н.И.; Тимошенко, Л.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The present paper reports the results of our investigation into physicochemical properties of the four much-used grades of nanodiamond powder (ASUD-50, ASUD-75, ASUD-95 and ASUD- 99). The analyzed powders differ in ratio of the structure components. It has been shown that as the surface of the ASUD-50 nanodiamond powder has a higher adsorbility activity than the ASUD-99 powde. These properties allow the powders to be used as adsorbents of biological media and catalysts for different oxidizing processes.